Creating an effective management system : integrating policy deployment, TWI, and Kata - Graupp, Patrick; Steward, Skip; Parsons, Brad (Roca Raton, FL : CRC Press, Taylor & Francis Group, a Productivity Press Book, 2020)
"The decades of experience-based wisdom that Graupp, Steward and Parsons share will set you on a new path to a more joyful organization and the tangible results it will produce." Rich Sheridan, CEO, Menlo Innovations; author of Joy, Inc. and Chief Joy Officer "A fine book by skilled practitioners that integrates Kata and TWI, with Strategy Deployment in pursuit of an integrated management system. Well done, Skip, Brad and Patrick." Pascal Dennis, president, Lean Pathways Inc.; author of Lean Production Simplified, Andy & Me, Andy & Me and the Hospital, Getting the Right Things Done, and The Remedy "In this practical and engaging book, Patrick Graupp, Skip Steward, and Brad Parsons give a concise and extremely clear explanation of what systems thinking looks like in a healthcare setting. And they do so in a way that translates easily to any type of organization. Highly recommended!" Alan Robinson, co-author of Ideas Are Free and The Idea-Driven Organization Despite the vast library of knowledge on Lean tools and models, the majority of Lean implementations fail to sustain themselves over time for lack of a functioning management system. In turn, when organizations try to apply a prescribed, one-size-fits-all, management system they inevitably find that what works for others may not work quite as well in their unique situation. Putting the right pieces in the right places is the prime challenge for every organization and no two successful management systems will, or should, be the same. This book provides and examines core principles that must be in place for an organization to find what an effective management system should constitute for them. It outlines key elements and how they work together as a necessary system to achieve overall success. Based on their extensive experience with organizational development and hands-on leadership in policy deployment, TWI and Kata, the authors describe their own journey in helping organizations discover and develop systems that function like well-designed and smooth-running machines while capturing the humanistic aspects of the foundational skills that emphasize the inherent synergy of the system. Readers will learn to help their own organizations "connect the dots" between the various pieces of Lean methodology and effectively create their own management systems that ultimately fulfil customers' needs and expectations.
OCLC-licensed vendor bibliographic record.
Keywords: Management; Organizational effectiveness; BUSINESS & ECONOMICS / Workplace Culture; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Production & Operations Management